Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1524-4741.2007.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-site Validation Trial of Radioactive Seed Localization as an Alternative to Wire Localization

Abstract: This study aims to validate radioactive seed localization (RSL) as an alternative to wire localization (WL) in the operative excision of nonpalpable breast lesions. Eligible patients were recruited sequentially. A sample of 99 patients treated with WL was compared to the next 383 patients treated with RSL. Margins were considered "negative" if > or =2 mm from in-situ and invasive disease. Pain and convenience scores were recorded on a 10-point scale. Patient characteristics and histology were similar. The lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 37 publications
(45 reference statements)
5
108
0
1
Order By: Relevance
“…The rate of positive margins in our study was 6%, which is at least comparable to the 8% rate reported by Gray et al (14)(15)(16)(17) and is well below the rate of 50,9% for excisions utilizing wire localization that was reported by Velanovic et al (29), both studies in non-palpable breast tumours. In a another prospective randomized trial of radioactive seed localization versus wire localization of non-palpable breast lesions, Hughes et al (30) found that radioactive seed localization resulted in a 35% relative improvement in the rate of negative margins in the first specimen and a 62% relative improvement in the rate of re-operation for positive margins.…”
Section: Lymph Node Statussupporting
confidence: 62%
See 3 more Smart Citations
“…The rate of positive margins in our study was 6%, which is at least comparable to the 8% rate reported by Gray et al (14)(15)(16)(17) and is well below the rate of 50,9% for excisions utilizing wire localization that was reported by Velanovic et al (29), both studies in non-palpable breast tumours. In a another prospective randomized trial of radioactive seed localization versus wire localization of non-palpable breast lesions, Hughes et al (30) found that radioactive seed localization resulted in a 35% relative improvement in the rate of negative margins in the first specimen and a 62% relative improvement in the rate of re-operation for positive margins.…”
Section: Lymph Node Statussupporting
confidence: 62%
“…Radioactive seed localisation was carried out as described by Gray et al (14)(15)(16)) using a titanium seed containing 7 Mbq of Iodine-125 ( 125 I). This radio nuclide has a half-life of 60 days and is a 27 keV source of gamma radiation.…”
Section: Radioactive Seed Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Great variation exists in the radiation dose administered for ROLL, with the literature quoting anywhere between 5 and 123 MBq, [12,13] whilst for RSL it is between 3.7 and 10.7 MBq [14,15]. ROLL requires localization to be performed within 24 h of surgery due to the short 6 h half-life of 99m Tc-labelled colloid and RSL typically is performed 0-5 days prior to surgery [7,[14][15][16][17].…”
mentioning
confidence: 99%